Economic forecasts and sovereign yields - Afonso, António (2013)
The European Commission releases twice a year economic forecasts for some macro and fiscal variables (GDP growth rate, inflation, budget balance, among others). In our research we will try to understand if the corrections made to these forecasts have an impact in sovereign yields. We will perform an econometric analysis in a panel of 15 EU countries (Austria, Belgium, Germany, Denmark, Spain, Finland, France, United Kingdom, Greece, Ireland, Italy, Luxembourg, Netherlands, Portugal and Sweden), covering the period from 1999:1 until 2012:1, and after we analyse each country individually, on the basis of a SUR analysis. We find that corrections in the EC’s forecasts do impinge on the 10-year sovereign bond yields, particularly corrections in fiscal variables, but this impact is different across countries, being more pronounced in countries with less favourable economic conditions.